2016
DOI: 10.1111/tbj.12604
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Metastases from Breast Cancer: Retrospective Analysis at an Academic Cancer Center

Abstract: Orbital metastases from breast cancer (BC) are rare, but often debilitating. BC accounts for nearly half of metastases to the orbit. Orbital metastases may be discovered years after the initial diagnosis of BC, and are rare at initial presentation. A search of the institutional data base at an academic cancer center identified BC patients who developed or presented with orbital metastases from 2000 to 2013. Baseline characteristics, treatment modalities, survival and treatment responses were collected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Pierson et al [15] reported in a retrospective study 20 cases of orbital metastases of breast cancer; the majority (80%) were ER-positive and Her2-negative and had a more favorable survival under treatment with hormone therapy. The frequency of metastases of breast cancer overexpressing ER can be explained biologically by the presence of estrogen receptors in hormone acting as target choroid tissue steroids for lacrimal secretion [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pierson et al [15] reported in a retrospective study 20 cases of orbital metastases of breast cancer; the majority (80%) were ER-positive and Her2-negative and had a more favorable survival under treatment with hormone therapy. The frequency of metastases of breast cancer overexpressing ER can be explained biologically by the presence of estrogen receptors in hormone acting as target choroid tissue steroids for lacrimal secretion [16].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy gives objective response rates of more than 70% according to various studies [15]. It may be used in doses of 30-50 Gy as a single treatment or in combination with chemotherapy and hormone therapy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Cancers arising from the lung, breast, and adrenal gland are thought to be frequent primary foci, whereas those from the colon have been only sporadically documented [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] . Even in breast cancers, orbital metastasis is estimated to occur in only 0.7% of cases, and its treatment strategy is yet to be determined [ 6 , 9 ]. Late metastasis is a very rare manifestation of cancers that can present more than 20 years after the initial diagnosis [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Metastases of solid tumors to the ocular and periocular structures are rare, yet they are estimated to account for approximately 1%–13% of all neoplasms found in the orbit. 1,2 Patients affected by these localizations of metastases usually have an abrupt onset of blurred vision, limited ocular motility, diplopia, and pain with important deterioration in their quality of life. Due to poor prognosis of patients affected by orbital metastases, primary aims of the treatment are symptom relief and preservation of visual functions.…”
Section: Introductionmentioning
confidence: 99%